Strange Aeons: Transhumanism, H.P. Lovecraft, and the affective index of posthuman dread - Bialecki, Jon (The Australian journal of anthropology, 2022)
New technologies open up the possibility of rapid social change the likes of which has not been seen since the appearance of anatomically modern humans: humanity being either substituted by or transformed into a new post-human species. Such an unprecedented change is difficult to concretely imagine in advance of its occurrence because it would unfold in a heretofore unheralded manner, and due to the speed with which it might happen, the only real indication of being on the cusp of such an even might be ‘affective indexes.’ For various reasons, models based on either Christian apocalyptic literature, the post-human academic turn, or science fiction are unreliable models of what these ‘affective indexes’ might be like. This essay explores whether horror literature in general and the writings of H.P. Lovecraft, in particular, might serve as models of what such ‘affective indexes’ of such a transformation might be and suggests that senses of disjunctures in scale, of time being ‘out of joint,’ of disturbing problematizations of what constitutes the human, and of religious horror and the sublime may be ways that humanity might anticipate the unthinkable prospect of being replaced.